Vpliv lastniških sort na trg hmelja ZDA v letih od 2000-2020 - MacKinnon, Douglas (visokošolska dela, 2022)
Changes in U.S. hop market dynamics between 1948 and 2020 were analyzed to establish baseline results and trends regarding the relationships between U.S. industry metrics such as production, stocks, stock depletion and season average price. Five data subpopulations were chosen based on unique market principles. The correlation using the Pearson method and the probability of causal relationships using the Bayesian theorem between industry metrics were calculated in such a way to demonstrate their evolution over time within the different periods. Comparisons between periods quantified the degree to which the U.S. hop market was influenced by the existence of intellectual property by 2020. Each variable was analyzed as both a dependent and independent variable in ways that measured their impact upon the events of future years. This enabled the development of a model for forecasting U.S. hop prices. Using the Herfindahl-Hirschman Index, the reduction of the competitiveness in the U.S. hop industry due to increased proprietary variety acreage between 2000 and 2020 was quantified. A hop cartel with influence over the acreage, production, supply and price of 70 percent of the U.S. hop industry by 2020 was documented. Forecasts for the years 2020 through 2025 demonstrated proprietary variety dominance of 90 percent of the U.S. industry by 2025 with 80 percent of U.S. acreage under the influence of one company. Evidence for the Delayed Surplus Response (DSR), a method by which disequilibrium in the hop market develops was identified and data demonstrating its effects between 1948 and 2000 were highlighted. Its absence during the period of rapid proprietary variety growth offered evidence regarding the existence and power of a cartel. The Hop Equilibrium Ratio (HER), a method for determining U.S. market equilibrium was presented and its effects upon price forecasting quantified. Price influence stemming from the existence of a hop cartel, the cost of deadweight losses and the potential effects of collusion between merchants and growers were discussed.
Keywords: Disertacije; Hmelj; hmeljski trg; intelektualna lastnina; kakovost; Lastniške sorte; sorte; tržna konkurenca